The impact of religion and traditions widespread among the population of kazakhstan on the changes that took place in society in the 18th-19th centuries in the context of the foreign policy of russia - Zhapekova, G. K.; Janguzhiyev, M. S.; Mukhangaliyeva, Zh. K.; Tastayeva, Zh. K.; Dshumagaliyeva, K. V.; Джангужиев, М. С. (European Journal of Science and Theology, 2020)
Interaction between countries, the necessity of strengthening intercultural ties and overcoming stereotypes and prejudices are among the key focus areas studied by researchers. The most interesting periods are those connected with civilizational fractures, when the influence of dominant cultures, colonial expansions in particular, had both positive and destructive impact on local traditions and customs. This article looks at the historical experience of interactions between traditional Kazakh society and neighbouring countries from the 19th to the early 20th century. The authors seek answers to the following questions: what response mechanisms could have been used for adaptation and preservation of unique characteristics of a certain culture? It is necessary to identify the role of religion in the development of religious education since as the Russian Empire expanded its colonies to the East it incorporated territories of countries that had practiced Islam for several centuries? The historical experience of coexistence of different peoples in this region shows that harmonious interaction between Christianity and Islam is possible Взаимодействие между странами, необходимость укрепления межкультурных связей и преодоления стереотипов и предрассудков входят в число ключевых направлений, изучаемых исследователями. Наиболее интересны периоды, связанные с цивилизационными разломами, когда влияние господствующих культур, в частности колониальной экспансии, оказывало как положительное, так и разрушительное воздействие на местные традиции и обычаи. В данной статье рассматривается исторический опыт взаимодействия традиционного казахского общества с соседними странами в XIX – начале XX века. Авторы ищут ответы на следующие вопросы: какие механизмы реагирования можно было использовать для адаптации и сохранения уникальных особенностей той или иной культуры? Необходимо определить роль религии в развитии религиозного образования, поскольку Российская империя по мере расширения своих колоний на Восток включала в себя территории стран, исповедовавших ислам на протяжении нескольких столетий? Исторический опыт сосуществования разных народов в этом регионе показывает, что гармоничное взаимодействие христианства и ислама возможно.
The impact of religion and traditions widespread among the population of kazakhstan on the changes that took place in society in the 18th-19th centuries in the context of the foreign policy of russia : g. K. Zhapekova, M. S. Janguzhiyev, Zh. K. Mukhangaliyeva, Zh. K. Tastayeva, K. V. Dshumagaliyeva. - Текст : непосредственный // European Journal of Science and Theology. - 2020. - Vol. 16. Iss. 4. - Р. 115-125 (Scopus). - ISSN 1841-0464
Keywords: импакт-фактор 2020; скопус; научный журнал; relations; периодическое издание; mullahs; дальнее зарубежье; interconfessional; религия; христианство; ислам; society; traditional